Morphological zeta-potential variation of nanoporous anodic alumina layers and cell adherence - Pedimonte, Birgit; Moest, Tobias; Luxbacher, Thomas; von Wilmowsky, Cornelius; Fey, Tobias; Schlegel, Andreas; Greil, Peter (Acta Biomaterialia, 2014)
Nanoscale surface modification of biomedical implant materials offers enhanced biological activity concerning protein adsorption and cell adherence. Nanoporous anodic alumina oxide (AAO) layers were prepared by electrochemical oxidation of thin Al-seed layers in 0.22 M C2H2O4, applying anodization voltages of 20-60 V. The AAO layers are characterized by a mean pore diameter varying from 15 to 40 nm, a mean pore distance of 40-130 nm, a total porosity of similar to 10% and a thickness of 560 +/- 40 nm. Zeta potential and isoelectric point (iep) were derived from streaming potential measurements and correlated to the topology variation of the nanoporous AAO layers. With decreasing pore diameter a shift of iep from similar to 7.9 (pore diameter 40 nm) to similar to 6.7 (pore diameter 15 nm) was observed. Plain alumina layers, however, possess an iep of similar to 9. Compared to the plain alumina surface an enhanced adherence and activity of hFOB cells was observed on the nanoporous AAO after 24 h culture with a maximum at a pore size of 40 nm. The topology-induced change of the electrochemical surface state may have a strong impact on protein adsorption as well as on cell adhesion, which offers a high potential for the development of bioactive AAO coatings on various biomaterial substrates. (C) 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights
Keywords: Nanoporous alumina; Zeta potential; Isoelectric point; Cell activity

Oxidative Crack Healing in Al2O3 Composites Loaded with Ti(2)AC (A = Al, Sn) Repair Fillers - Pedimonte, Birgit; Bei, Guoping; Pourjafar, D.; Fey, Tobias; Greil, Peter (Journal of Ceramic Science and Technology, 2014)
Crack healing of alumina composites loaded with 5, 10, and 20 vol% Ti(2)AC (A = Al or Sn) MAX phase was investigated. Surface cracks were prepared by means of indent loading and the modulus of rupture was measured on virgin, indented, and healed specimens. The MAX phase particles serve as repair filler which reacts with oxygen penetrating along a surface crack and filling disrupted crack surfaces with the oxidation reaction products. After annealing for 3 h composites loaded with 20 vol /0 Ti(2)A1C showed full recovery at a healing temperature of approximately 900 degrees C, whereas lower temperatures of 700 C were observed for specimens loaded with 10 and 20 vol% Ti2SnC. The enhanced healing response of Ti(2)AC-loaded composites containing Sn instead of Al on the A-position offers high potential for providing crack healing capability to ceramic matrix composites applied at moderate temperatures below 1000 degrees C.
Keywords: MAX phase composites; crack healing; repair filler; alumina; oxidation

The influence of nanoporous anodic aluminum oxide on the initial adhesion of Streptococcus mitis and mutans - Taxis, Jürgen; von Wilmowsky, Cornelius; Pedimonte, Birgit; Beuscher, Horst-Ulrich; Ries, Jutta; Kesting, Marco Rainer; Möst, Tobias (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2019)
The use of nanoscale surface modifications offers a possibility to regulate the bacterial adherence behavior. The aim of this study was to evaluate the influence of nanoporous anodic aluminum oxide of different pore diameters on the bacterial species Streptococcus mitis and Streptococcus mutans. Nanoporous anodic aluminum oxide (AAO) surfaces with an average pore diameter of 15 and 40 nm, polished pure titanium and compact aluminum oxide (alumina) samples as reference material were investigated. S. mitis and mutans were evaluated for initial adhesion and viability after an incubation period of 30 and 120 min. After 30 min a significantly reduced growth of S. mitis and mutans on 15 nm samples compared to specimens with 40 nm pore diameter, alumina and titanium surfaces could be observed (p <.001). Even after 120 min incubation there was a significant difference between the surfaces with 15 nm pore diameter and the remaining samples (p <.001). AAO surfaces with a small pore diameter have an inhibitory effect on the initial adhesion of S. mitis and mutans. The use of such pore dimensions in the area of the implant shoulder represents a possibility to reduce the adhesion behavior of these bacterial species.
CRIS-Team Scopus Importer:2019-12-03
Keywords: biofilm; initial adhesion; nanoporous anodic aluminum oxide; Streptococcus mitis; Streptococcus mutans